프러시안블루의 LBL(Layer-by-Layer) 합성법에 의한 알지네이트 비드형 흡착제의 세슘 흡착 특성연구 - 김복성(Bok Seong Kim); 강성원(Sung Won Kang) (Daehan hwan'gyeong gonghag hoeji, 2021)
목적:원전사고나 방사능 폐기물 유출에 의한 방사성 오염물질의 수계 확산시 수중 세슘(Cs)을 선택적으로 흡착할 수 있는 비드형 흡착제를 개발하고자 하였다. 방법:알지네이트를 지지체로 하고 PB를 고정화한 PA(prussian blue-Alginate bead) 비드와 PB를 다중고정화 방식인 Layer-by-Layer(LBL) 합성법으로 PB를 고정화된 PAL(Prussian blue-Alginate bead with LBL synthesis) 비드를 개발하였다. 결과 및 토의:SEM(EDS) 및 TG 분석을 통해 LBL 합성법이 적용된 PAL 비드가 PA 비드와 비교하여 PB 함량이 6.31% 향상된 것을 확인하였다. 개발 흡착제의 세슘 흡착성능을 평가하였는데, PA 비드의 최대흡착량(qm)이 25.783 mg/g이었고 PAL 비드는 28.294 mg/g으로 확인되어 LBL 합성방법에 의해 Cs 흡착능이 향상된 것을 확인하였다. 또한 흡착제의 안정성을 판단하기 위해 PA 비드 및 PAL 비드의 합성 이후 세척수를 UV-vis 분석한 결과, PAL 비드의 PB 탈착이 더 낮게 나타나 LBL 합성으로 안정성도 향상된 것을 확인하였다. 결론:본 연구에서는 수중에 존재하는 Cs을 선택적으로 흡착하기 위한 흡착제를 개발하기 위해 알지네이트 비드 내 PB를 화학적으로 고정화한 흡착제를 개발하였다. PB 고정화는 LBL 합성법을 적용하여 진행하였고 최종적으로 PAL 비드의 최대흡착량(qm)은 28.294 mg/g으로 나타나 방사성 세슘 오염수에 효과적이고 안정적으로 적용될 수 있을 것으로 기대된다. Objectives:The purpose of this study was to develop an adsorbent to which Prussian blue (PB) is stably immobilized to remove radioactive cesium (Cs). Methods:Prussian blue-Alginate (PA) bead and Prussian blue-Alginate with Layer-by-layer synthesis (PAL) bead were synthesized by immobilizing PB respectively. Results and Discussion:As a results of XRD and FT-IR analysis, PB was successfuuly immobilized in alginate bead and PA, PAL bead. SEM (EDS) and TG analysis data were confirmed that the PB content of the PAL bead to which the LBL synthesis method was applied was improved by 6.31%. It was confirmed that the Cs adsorption capacity was improved through the LBL assembly process. The maximum adsorption amount (qm) of PA bead was 25.783 mg/g, and PAL　bead was mg/g. In addition, as a result of UV-vis analysis of washing water after synthesis of PA bead and PAL bead, it was confirmed that the PB desorption of the PAL bead was lower indicating that the stability was also improved by LBL synthesis. Conclusions:We developed an adsorbent which prussianblue immobilized on alginate bead for selective removal cesium in aqueous solution. PB was immobilized by LBL synthesis method qm of PAL beads was 28.294 mg/g. It was expected to applied effectively and stably to radioactive cesium contaminated water. KCI Citation Count: 0